2019
DOI: 10.1002/stem.3091
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Phosphoenolpyruvate Carboxykinase Regulates Osteogenic Differentiation by Modulating AMPK/ULK1-Dependent Autophagy

Abstract: Mitochondrial phosphoenolpyruvate carboxykinase (PCK2) is a rate‐limiting enzyme that plays critical roles in multiple physiological processes. The decompensation of PCK2 leads to various energy metabolic disorders. However, little is known regarding the effects of PCK2 on osteogenesis by human mesenchymal stem cells (hMSCs). Here, we report a novel function of PCK2 as a positive regulator of MSCs osteogenic differentiation. In addition to its well‐known role in anabolism, we demonstrate that PCK2 regulates au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 53 publications
1
29
0
Order By: Relevance
“…These factors containing of age and the estrogen depletion would bring changes to the microenvironment of the bone marrow cavity, which can lead to increase of adipose formation and inhibition of bone formation [31]. We observed that PCK2 could promote osteogenic differentiation of MSCs previously [18] and indicated that PCK2 could suppress the adipogenic differentiation of MSCs in this study, so we further determined the effect of lentivirus-mediated PCK2 overexpression on osteoporosis of mice caused by OVX and aging. Our previous work showed that PCK2 regulates osteogenic differentiation of MSCs through AMPK/ULK1-dependent autophagy [18], giving us the clue to explore the role of autophagy in the regulation of PCK2 reversing the bone loss of osteoporotic mice.…”
Section: Pck2 Suppressed Adipogenic Differentiation Of Bmmscs In Vivomentioning
confidence: 64%
See 3 more Smart Citations
“…These factors containing of age and the estrogen depletion would bring changes to the microenvironment of the bone marrow cavity, which can lead to increase of adipose formation and inhibition of bone formation [31]. We observed that PCK2 could promote osteogenic differentiation of MSCs previously [18] and indicated that PCK2 could suppress the adipogenic differentiation of MSCs in this study, so we further determined the effect of lentivirus-mediated PCK2 overexpression on osteoporosis of mice caused by OVX and aging. Our previous work showed that PCK2 regulates osteogenic differentiation of MSCs through AMPK/ULK1-dependent autophagy [18], giving us the clue to explore the role of autophagy in the regulation of PCK2 reversing the bone loss of osteoporotic mice.…”
Section: Pck2 Suppressed Adipogenic Differentiation Of Bmmscs In Vivomentioning
confidence: 64%
“…Autophagy is a conserved physical process which is essential for cell survival, differentiation, development, and homeostasis [33]. Our previous study suggested that PCK2 regulates osteogenic differentiation of MSCs through modulating autophagy [18]. We further investigated whether PCK2 could rescue the regenerative capability of endogenous BMMSCs in OVX and aged mice through autophagy.…”
Section: Pck2 Suppressed Adipogenic Differentiation Of Bmmscs In Vivomentioning
confidence: 97%
See 2 more Smart Citations
“…Studies have also shown that AMPK may induce autophagy by directly activating ULK1 or inhibiting mTOR [ 15 ]. Activation of the AMPK/ULK1-dependent autophagy can be correlated positively with osteogenic differentiation of MSCs [ 20 , 21 ], and ULK1 overexpression or rapamycin can activate autophagy and then notably elevate the osteoblast differentiation activity and restore the bone volume [ 22 ].…”
Section: Introductionmentioning
confidence: 99%